Trend and Predictors of Short-term Mortality of Adult Bacteremia at Emergency Departments: A 14-Year Cohort Study of 14 625 Patients. (6th October 2021) - Chiang, Hsiu-Yin; Chen, Tsung-Chia; Lin, Che-Chen; Ho, Lu-Ching; Kuo, Chin-Chi; Chi, Chih-Yu
Abstract: Background: Bacteremia is a life-threatening condition with a high mortality rate in critical care and emergency settings. The current study investigated the trend of mortality and developed predictive models of mortality for adults with bacteremia at emergency departments (EDs). Methods: We conducted a retrospective cohort study of adults with bacteremia at the ED of China Medical University Hospital. Patient data were obtained from the Clinical Research Data Repository, and mortality information was obtained from the National Death Registry. We developed a new model to predict 7-day mortality in the derivation population and compared the model performance of the new model with Pitt Bacteremia Score (PBS) and Bloodstream Infection Mortality Risk Score (BSIMRS) in the validation population. Results: We identified 14625 adult patients with first-time bacteremia at the ED, of whom 8.4% died within 7 days. From 2003 to 2016, both the cumulative incidence and 7-day mortality rate of bacteremia decreased significantly. The ED bacteremia mortality (ED-BM) model included PBS parameters, age, infection source, baseline steroid use, and biochemical profiles (estimated glomerular filtration rate, platelet, blood urea nitrogen, potassium, and hemoglobin) for predicting 7-day mortality. The discrimination performance of the ED-BM model (area under curve [AUC], 0.903) was significantly better than that of PBS (AUC, 0.848) or BSIMRS (AUC, 0.885). Conclusions: Although the cumulative incidence and mortality of ED bacteremia decreased, its mortality burden remains critical. The proposed ED-BM model had significantly better model performance than other scoring systems in predicting short-term mortality for adult patients with bacteremia at EDs.